2018
DOI: 10.1248/bpb.b18-00026
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mouse RANKL Antibodies Inhibit Alveolar Bone Destruction in Periodontitis Model Mice

Abstract: Denosumab is an anti-bone resorptive drug consisting of complete human monoclonal antibodies that targets receptor activator of nuclear factor κB ligand (RANKL), which is responsible for osteoclast formation. The drug has been adapted for bone diseases, such as osteoporosis and bone metastasis related to cancer, but is not used for alveolar bone destruction related to periodontitis. In the present study, we aimed to clarify whether denosumab prevents bone destruction associated with lipopolysaccharide (LPS)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Long-lasting hyperglycemia also promotes the proliferation and differentiation of osteoclasts, resulting in bone tissue more susceptible to resorption [ 31 , 32 ]. RANKL Ab and miR146a have been proven to negatively modulate inflammatory responses in the periodontium or periodontal cells [ 33 , 34 ]. Local RANKL Ab or miR146a administration can inhibit osteoclast formation and reduce bone destruction in inflammatory diseases [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting hyperglycemia also promotes the proliferation and differentiation of osteoclasts, resulting in bone tissue more susceptible to resorption [ 31 , 32 ]. RANKL Ab and miR146a have been proven to negatively modulate inflammatory responses in the periodontium or periodontal cells [ 33 , 34 ]. Local RANKL Ab or miR146a administration can inhibit osteoclast formation and reduce bone destruction in inflammatory diseases [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These classical pro-inflammatory markers of periodontitis present potential therapeutic target for periodontitis treatment 50 , 51 . In this regard, several studies demonstrated that pharmacological treatments, including the use of synthetic drugs and natural compounds, such as TNF-α antagonist 52 , angiotensin II receptor blocker 53 , non-selective β-blocker 54 or anti-RANKL antibodies 55 , resulted in reduced levels of TNF-α, NF-κB and RANKL, thereby, resolving experimental periodontitis in vivo . The use of such aforementioned conventional pharmacological drugs in periodontal therapy is not devoid of side effects, thus, necessitating the development of novel therapeutic agents and strategies to provide safer alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…2; MINITOR CO., Ltd. Tokyo, Japan), standard rotary (M212H; MINITOR CO., Ltd. Tokyo, Japan), and 1-mm round bur, with the mice given the same mixed anesthetic noted above. Tooth elongation process X-ray photography was performed with an in vivo μCT system (R_mCT2; Rigaku Co., Ltd., Tokyo, Japan) at 1 and 2 weeks after defacement 51 . Incisor elongation rate was determined by measuring from the alveolar bone crest to middle of the round lesion using the Image J software package, version 1.52a (National Institutes of Health, Maryland, United States).…”
Section: Methodsmentioning
confidence: 99%